'Together in the tech trenches': a view of Israel's innovation culture. Issue 3 (3rd July 2021) - Yeshua-Katz, Daphna; Efrat-Treister, Dorit
ABSTRACT: The Israeli defence industry is a frequently cited factor when explaining Israeli's innovation success. This, however, only partly explains why so much innovation is occurring in one place. We focus on the cultural values most relevant to predicting innovation – in-group collectivism, power distance, and uncertainty avoidance – We then illustrate, in two studies, how these cultural values combined with four local factors that might be responsible for the Israeli culture of innovation: the Israeli defence industry, determined informality, an anti-hierarchical culture, and hubris. In addition to these four local factors, we predict that a mix of Western-Eastern culture and leadership values such as medium level of in-group collectivism, low power distance, and low uncertainty avoidance lead to high levels of innovation. In Study 1, we interview a panel of six experts who are key figures in the Israeli information technology industry; In Study 2, we survey thirty MBA students, asking them about the sources of Israel's innovation culture.Theoretically, our study proposes a new look at innovation from a cultural perspective. By extending previous research, this study highlights the way in which the combination of collectivistic Eastern and individualistic Western cultures, accompanied with the four local factors examined, leads to exceptionally high levels of innovation. Empirically, this study reveals the cultural and local aspects that may contribute to the development of innovation clusters worldwide.